Multigenerational exposure to per- and polyfluoroalkyl substances (PFAS) negatively impacts the reproductive health of male mice - Leah Gillespie; Jacinta H. Martin; Amanda L. Anderson; Natalie A. Trigg; John E. Schjenken; Shannon P. Smyth; Ilana R. Bernstein; Simone J. Stanger; Logan McElhone; Colin C. Conine; Fay Waldrip; Erin J. Campbell; et al. (Environmental Research, 2026)

The pink Amazon?’ Metabarcoding reveals Rhodolith beds as hidden hotspots of global marine biodiversity - Pedro A.S. Longo; Gustavo M. Mori; Cintia P. Targueta; Mariana P. de C. Telles; Cinthya Simone Gomes Santos; Flávio Dias Passos; André R. Senna; Guilherme H. Pereira-Filho (Biological Conservation, 2026)

When Scientific Reassessment Fails Citizen Science. Comment on Soldo, A. When Citizen Science Becomes Speculation: Evaluating the Reliability of Lamnid Shark Identification from Photographic Records in the Mediterranean. J. Mar. Sci. Eng. 2026, 14, 173 - Patrick L. Jambura; Julia Türtscher; Joshua K. Moyer; Kenshu Shimada; Ilija Ćetković; Branko Dragičević; Pero Ugarković; Mišo Pavičić; Phillip C. Sternes; Simone Niedermüller; Jacopo Bernardi; Matteo Barbato; et al. (Journal of Marine Science and Engineering, 2026)
Soldo [...]

A high-resolution record of early rift development and tectonic, sedimentary and environmental conditions in an active rift basin: IODP MSP drilling in the Corinth Rift, Greece (Expedition 381) - Lisa C. McNeill; Donna J. Shillington; Jeanine Ash; Gareth D.O. Carter; Richard E.Ll. Collier; Aleksandra Cvetkoska; Paula Diz; Mai-Linh Doan; Jeremy D. Everest; Natacha Fabregas; Eugenia Fatourou; Mary Ford; et al. (Marine Geology, 2026)

A dataset of plant communities invaded by Acacia sp. pl. and Robinia pseudoacacia in Italy - Eugenia Siccardi; Alice Misuri; Alicia Teresa Rosario Acosta; Claudia Angiolini; Dario Azzaro; Gianluigi Bacchetta; Simonetta Bagella; Elena Barni; Giuseppe Bazan; Maria E. Boi; Gianmaria Bonari; Giuseppe Brundu; et al. (Plant Biosystems, 2026)
The full extent of the ecological threat posed by non-native invasive leguminous N-fixing trees to Italian ecosystems has not been thoroughly documented at the national level. This study, conducted by the Working Group on Alien Species of the Italian Botanical Society, aims to develop a comprehensive dataset that provides information on invaded and non-invaded areas, supporting multi-scale ecological analyses on the impact of black locust ( Robinia pseudoacacia ) and different Acacia sensu lato species across Italy. We conducted paired vegetation surveys across 18 distinct invasion contexts, comparing invaded and non-invaded plant communities. These invasion contexts were selected opportunistically by the participating research groups, based on the availability of well-documented sites where the focal species were already established and exerting ecologically relevant effects. Overall, we conducted 342 vegetation surveys across 10 Italian administrative regions and identified 824 plant species. Our surveys highlighted areas affected by five invasive species, including A. dealbata, A. mearnsii, A. saligna , Vachellia karroo , and R. pseudoacacia . Most of the surveys focused on areas invaded by A. saligna . The plant formations investigated fall under 23 EUNIS habitat codes and 10 Natura 2000 habitats. The most frequently occurring vegetation types under the EUNIS code are temperate and Mediterranean-montane scrub, and the most frequently investigated habitat is priority habitat 2250*: Coastal dunes with Juniperus sp. pl. This dataset provides a robust baseline that can facilitate more detailed assessments of the impacts of these invasive species on native ecosystems.

Non-native mollusc species in Brazil: a first national inventory and distributional overview - Fabrizio Marcondes Machado; Rodrigo B. Salvador; Igor C. Miyahira; Luiz Ricardo Lopes de Simone; Tarcilla C. de Lima; Mariana Osório Côrtes; Julia D. Sigwart; Angie Patiño Montoya; Vanessa S. Amaral; Paula Spotorno; Marcel Sabino Miranda; Augusto L. Ferreira Júnior; et al. (Biological Invasions, 2026)

The Italian effort toward a coordinated observation of Essential Variables (EOV, ECV, EBV) in European Marine Environments. Long-term observation in the central Mediterranean seas and Italian coasts - Simone Toller; Emilio Urbinati; Debora Bellafiore; Caterina Bergami; Francesca De Pascalis; Marcello G. Magaldi; Marco Bellacicco; Federico Bellati; Maristella Berta; Angelo Boccacci; Roberto Bozzano; Fabio Brunetti; et al. (Frontiers in Marine Science, 2026)
Monitoring Essential Ocean, Climate, and Biodiversity Variables (EOVs, ECVs and EBVs) collected through the marine Research Infrastructures (RIs) is critical for assessing environmental status, improving scientific knowledge and defining environmental policies. This study evaluates the capacity of the Italian marine monitoring system, including facilities such as fixed stations, buoys, autonomous platforms, and mobile systems across the Mediterranean Sea, to produce those variables. Conducted in 2023 within the framework of the ITINERIS project ( https://itineris.cnr.it/ ), which aims to strengthen coordination among national and ESFRI RIs (European Strategy Forum on Research Infrastructures), the analysis systematically examines the spatial, thematic, and technological coverage of EOVs, ECVs, EBVs observations and their alignment with international standards for environmental monitoring of 155 facilities from eight Italian and pan-European marine RIs. Of the 107 EVs recognized, 50% were actively produced by the RIs considered, with over 90% meeting the established requirements for EVs. These numbers will be updated to reflect the new equipment acquired during the project’s implementation up to early 2026, which is expected to boost EVs production by approximately 38-40%. The national monitoring network demonstrates a high degree of maturity for oceanic and climate variables, while biodiversity observations remain less represented, indicating the need for further technological innovation and automation. These findings emphasize the importance of enhancing coordination and harmonization among RIs to ensure balanced and interoperable monitoring. The study provides key recommendations to strengthen Italy’s capacity to contribute to the global characterization of EOVs, ECVs, and EBVs and to support evidence-based environmental assessments and the development of robust environmental management strategies at European level.

Ecotoxicological effects of drilling cuttings waste from oil wells: sensitivity of soil invertebrates and plants - Dara C. M. V. P. da Cruz; Higor E. F. Lorin; Fabrielle P. dos Reis; Cibele A. de Costa; Simone B. da Fontoura; Heraldo N. de Souza; Everaldo Zonta; Júlia C. Niemeyer (Ecotoxicology, 2026)

Barcoding‐Inferred Biodiversity of Shallow‐Water Indo‐Pacific Demosponges - Dirk Erpenbeck; Adrian Galitz; Michael L. Berumen; Gabriele Büttner; Cécile Debitus; Moritz Dirnberger; Merrick Ekins; Kathryn Hall; Leonard Namuth; Sylvain Petek; Neda Rahnamae; Maggie M. Reddy; et al. (Journal of Biogeography, 2026)
Aim The Indo‐Pacific is the world's largest marine biogeographic region. It is characterised by different degrees of connectivity among its subregions and harbours the majority of demosponge species currently known to science. Comparisons between regional sponge faunas have been undertaken in the past, mostly based on morphological species identification. The Sponge Barcoding Project, in tandem with regional DNA taxonomy campaigns, provides one of the largest DNA‐based taxonomic data collections from sponges of the Indo‐Pacific. Here, we utilise the barcoding data in the most extensive molecular biodiversity study of sponges to date, which reveals patterns of shallow‐water demosponge faunal connectivity, endemism and distribution in the Indo‐Pacific with a level of resolution unavailable in prior morphology‐based studies. Location Demosponge specimens in this study cover 13 marine provinces (MPs) of the Indo‐Pacific. Methods We classified demosponge barcodes from 1910 sponge samples into 701 molecular operational taxonomic units (MOTUs) using 28S rRNA. MOTU composition of the MPs was compared based on Jaccard and Sørenson dissimilarities and other biodiversity indices. Results Our data corroborated high endemism in MPs (up to 84.1% endemic MOTUs). Faunal overlaps are between the Red Sea and the Gulf, which displayed small connectivity with other MPs in the Western Indian Ocean. The Western Indian Ocean is a strong faunistic boundary to the Central Indo‐Pacific, to which the Polynesian sponge faunas were comparatively isolated as well. Main Conclusions Our data corroborate case studies on sponges that generally reject the presence of cosmopolitan or otherwise widespread sponge species, instead revealing high levels of regional endemism. This is consistent with similar observations and hypotheses in other marine invertebrates, and highlights the need for close regional monitoring to identify biodiversity changes. Connectivity among Indo‐Pacific MPs differs for demosponges in many aspects from that of other marine taxa, hypothetically due to their shorter pelagic larval phase.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Definition and performance of acoustic personalised environmental control systems (acoustic PECS): A systematic review - Simone Torresin; Larissa Pereira de Souza; Seda Yuksel Dicle; Douaa Al-Assaad; Francesco Aletta; Alvaro Balderrama; Mariya P. Bivolarova; Pyoung-Jik Lee; Josep Llorca-Bofí; Henna Maula; Alessandra Luna Navarro; Ilaria Pigliautile; et al. (Building and Environment, 2025)

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Current state of plant conservation translocations across Europe: motivations, challenges and outcomes - Sandrine Godefroid; Sam Lacquaye; Andreas Ensslin; Sarah Dalrymple; Thomas Abeli; Hannah Branwood; Inmaculada Ferrando Pardo; P. Pablo Ferrer Gallego; Elke Zippel; Luísa Gouveia; Carlos Alberto Lobo; Francisco Fernandes; et al. (Biodiversity and Conservation, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Water-soluble amino acid derivatives isolated from cultures of three fungal strains - Matheus Gotha; Gabriel C. Junqueira; Ariane F. Bertonha; Julie P.G. Rodríguez; Juliana R. Gubiani; Emanuele F. Pissinati; Rafaely N. Lima; Lara D. Sette; Simone P. de Lira; Luciane F.P. Oliveira; Andrea N.L. Batista; João M. Batista; et al. (Phytochemistry Letters, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

LP-31 A straightforward protocol to generate human stem cell-derived astrocytes for the in vitro strategy to predictive neurotoxicity profiles - U. De Simone; F. Caloni; P. Pignatti; T. Coccini (Toxicology Letters, 2024)

Enhancing Tree Performance Through Species Mixing: Review of a Quarter-Century of TreeDivNet Experiments Reveals Research Gaps and Practical Insights - Leen Depauw; Emiel De Lombaerde; Els Dhiedt; Haben Blondeel; Luis Abdala-Roberts; Harald Auge; Nadia Barsoum; Jürgen Bauhus; Chengjin Chu; Abebe Damtew; Nico Eisenhauer; Marina V. Fagundes; et al. (Current Forestry Reports, 2024)

Purple pitanga extract (Eugenia uniflora) attenuates oxidative stress induced by MPTP - Eduarda Monteiro Fidelis; Anne Suely P. Savall; Jhuly Dornelles Mello; Caroline Brandão Quines; Antônio Alvenir Comis-Neto; Tuane Bazanella Sampaio; Cristiane Casagrande Denardin; Daiana Silva de Ávila; Suzan Gonçalves Rosa; Simone Pinton (Metabolic Brain Disease, 2023)

Enhanced root growth and nitric oxide content in ‘Mandarin’ lime under drought stress: experimental evidence - Neidiquele M. Silveira; Maria Isabel M. de Oliveira; Simone F. da Silva; Marcela T. Miranda; Matheus P. Passos; Eduardo C. Machado; Rafael V. Ribeiro (Brazilian Journal of Botany, 2023)

Study of fast in-line measurement techniques for water ice characterization - Carolina Cruz; Cláudio P. Fonte; Antonio De Simone; Felix K. Oppong; Will Jeatt; Thomas L. Rodgers (Journal of Food Engineering, 2023)

Trait interactions effects on tropical tree demography depend on the environmental context - Vitor de A. Kamimura; Priscilla de P. Loiola; Carlos P. Carmona; Marco A. Assis; Carlos A. Joly; Flavio A.M. Santos; Simone A. Vieira; Luciana F. Alves; Valéria F. Martins; Eliana Ramos; Rafael F. Ramos; Francesco de Bello (Perspectives in Plant Ecology, Evolution and Systematics, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

A large share of Berlin’s vegetable consumption can be produced within the city - Marion De Simone; Prajal Pradhan; Jürgen P. Kropp; Diego Rybski (Sustainable Cities and Society, 2023)

Perceptual and Acoustic Analysis of Speech in Spinocerebellar ataxia Type 1 - Teije van Prooije; Simone Knuijt; Judith Oostveen; Kirsten Kapteijns; Adam P. Vogel; Bart van de Warrenburg (The Cerebellum, 2023)
This study characterizes the speech phenotype of spinocerebellar ataxia type 1 (SCA1) using both perceptual and objective acoustic analysis of speech in a cohort of SCA1 patients. Twenty-seven symptomatic SCA1 patients in various disease stages (SARA score range: 3–32 points) and 18 sex and age matched healthy controls underwent a clinical assessment addressing ataxia severity, non-ataxia signs, cognitive functioning, and speech. Speech samples were perceptually rated by trained speech therapists, and acoustic metrics representing speech timing, vocal control, and voice quality were extracted. Perceptual analysis revealed reduced intelligibility and naturalness in speech samples of SCA1 patients. Acoustically, SCA1 patients presented with slower speech rate and diadochokinetic rate as well as longer syllable duration compared to healthy controls. No distinct abnormalities in voice quality in the acoustic analysis were detected at group level. Both the affected perceptual and acoustic variables correlated with ataxia severity. Longitudinal assessment of speech is needed to place changes in speech in the context of disease progression and potential response to treatment.

Long-term changes in benthic communities following the invasion by an alien octocoral in the Southwest Atlantic, Brazil - Lécio de Carvalho-Junior; Leonardo M. Neves; Tatiana P. Teixeira-Neves; Simone J. Cardoso (Marine Pollution Bulletin, 2023)

Antarctic Strain of Rhodotorula mucilaginosa UFMGCB 18,377 Attenuates Mucositis Induced by 5-Fluorouracil in Mice - Joana O. P. A. Coutinho; Mônica F. Quintanilha; Marina R. A. Campos; Enio Ferreira; Graciéle C. A. de Menezes; Luiz H. Rosa; Carlos A. Rosa; Katia D. Vital; Simone O. A. Fernandes; Valbert N. Cardoso; Jacques R. Nicoli; Fabiana C. P. Tiago; et al. (Probiotics and Antimicrobial Proteins, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Genetic testing and surveillance in infantile myofibromatosis: a report from the SIOPE Host Genome Working Group - Simone Hettmer; Guillaume Dachy; Guido Seitz; Abbas Agaimy; Catriona Duncan; Marjolijn Jongmans; Steffen Hirsch; Iris Kventsel; Uwe Kordes; Ronald R. de Krijger; Markus Metzler; Orli Michaeli; et al. (Familial Cancer, 2021)
Infantile myofibromatosis (IM), which is typically diagnosed in young children, comprises a wide clinical spectrum ranging from inconspicuous solitary soft tissue nodules to multiple disseminated tumors resulting in life-threatening complications. Familial IM follows an autosomal dominant mode of inheritance and is linked to PDGFRB germline variants. Somatic PDGFRB variants were also detected in solitary and multifocal IM lesions. PDGFRB variants associated with IM constitutively activate PDGFRB kinase activity in the absence of its ligand. Germline variants have lower activating capabilities than somatic variants and, thus, require a second cis-acting hit for full receptor activation. Typically, these mutant receptors remain sensitive to tyrosine kinase inhibitors such as imatinib. The SIOPE Host Genome Working Group, consisting of pediatric oncologists, clinical geneticists and scientists, met in January 2020 to discuss recommendations for genetic testing and surveillance for patients who are diagnosed with IM or have a family history of IM/ PDGFRB germline variants. This report provides a brief review of the clinical manifestations and genetics of IM and summarizes our interdisciplinary recommendations.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Effects of Nutrient Management Scenarios on Marine Food Webs: A Pan-European Assessment in Support of the Marine Strategy Framework Directive - Chiara Piroddi; Ekin Akoglu; Eider Andonegi; Jacob W. Bentley; Igor Celić; Marta Coll; Donna Dimarchopoulou; René Friedland; Kim de Mutsert; Raphael Girardin; Elisa Garcia-Gorriz; Bruna Grizzetti; et al. (Frontiers in Marine Science, 2021)
Eutrophication is one of the most important anthropogenic pressures impacting coastal seas. In Europe, several legislations and management measures have been implemented to halt nutrient overloading in marine ecosystems. This study evaluates the impact of freshwater nutrient control measures on higher trophic levels (HTL) in European marine ecosystems following descriptors and criteria as defined by the Marine Strategy Framework Directive (MSFD). We used a novel pan-European marine modeling ensemble of fourteen HTL models, covering almost all the EU seas, under two nutrient management scenarios. Results from our projections suggest that the proposed nutrient reduction measures may not have a significant impact on the structure and function of European marine ecosystems. Among the assessed criteria, the spawning stock biomass of commercially important fish stocks and the biomass of small pelagic fishes would be the most impacted, albeit with values lower than 2.5%. For the other criteria/indicators, such as species diversity and trophic level indicators, the impact was lower. The Black Sea and the North-East Atlantic were the most negatively impacted regions, while the Baltic Sea was the only region showing signs of improvement. Coastal and shelf areas were more sensitive to environmental changes than large regional and sub-regional ecosystems that also include open seas. This is the first pan-European multi-model comparison study used to assess the impacts of land-based measures on marine and coastal European ecosystems through a set of selected ecological indicators. Since anthropogenic pressures are expanding apace in the marine environment and policy makers need to use rapid and effective policy measures for fast-changing environments, this modeling framework is an essential asset in supporting and guiding EU policy needs and decisions.

Evaluation of climate simulations produced with the Brazilian global atmospheric model version 1.2 - Caio A. S. Coelho; Dayana C. de Souza; Paulo Y. Kubota; Simone M. S. Costa; Layrson Menezes; Bruno S. Guimarães; Silvio N. Figueroa; José P. Bonatti; Iracema F. A. Cavalcanti; Gilvan Sampaio; Nicholas P. Klingaman; Jessica C. A. Baker (Climate Dynamics, 2021)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Rare earth elements (REE) in biology and medicine - P. Ascenzi; M. Bettinelli; A. Boffi; M. Botta; G. De Simone; C. Luchinat; E. Marengo; H. Mei; S. Aime (Rendiconti Lincei. Scienze Fisiche e Naturali, 2020)
This survey reports on topics that were presented at the workshop on “Challenges with Rare Earth Elements. The Periodic Table at work for new Science & Technology” hold at the Academia dei Lincei in November 2019. The herein reported materials refer to presentations dealing with studies and applications of rare earth elements (REE) in several areas of Biology and Medicine. All together they show the tremendous impact REE have in relevant fields of living systems and highlight, on one hand, the still existing knowledge gap for an in-depth understanding of their function in natural systems as well as the very important role they already have in providing innovative scientific and technological solutions in a number of bio-medical areas and in fields related to the assessment of the origin of food and on their manufacturing processes. On the basis of the to-date achievements one expects that new initiatives will bring, in a not too far future, to a dramatic increase of our understanding of the REE involvement in living organisms as well as a ramp-up in the exploitation of the peculiar properties of REE for the design of novel applications in diagnostic procedures and in the set-up of powerful medical devices. This scenario calls the governmental authorities for new responsibilities to guarantee a continuous availability of REE to industry and research labs together with providing support to activities devoted to their recovery/recycling.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Correction to: Rewiring of glucose metabolism defines trained immunity induced by oxidized low-density lipoprotein - Samuel T. Keating; Laszlo Groh; Kathrin Thiem; Siroon Bekkering; Yang Li; Vasiliki Matzaraki; Charlotte D. C. C. van der Heijden; Jelmer H. van Puffelen; Ekta Lachmandas; Trees Jansen; Marije Oosting; L. Charlotte J. de Bree; et al. (Journal of Molecular Medicine, 2020)

Rewiring of glucose metabolism defines trained immunity induced by oxidized low-density lipoprotein - Samuel T. Keating; Laszlo Groh; Kathrin Thiem; Siroon Bekkering; Yang Li; Vasiliki Matzaraki; Charlotte D. C. C. van der Heijden; Jelmer H. van Puffelen; Ekta Lachmandas; Trees Jansen; Marije Oosting; L. Charlotte J. de Bree; et al. (Journal of Molecular Medicine, 2020)
Stimulation of monocytes with microbial and non-microbial products, including oxidized low-density lipoprotein (oxLDL), induces a protracted pro-inflammatory, atherogenic phenotype sustained by metabolic and epigenetic reprogramming via a process called trained immunity . We investigated the intracellular metabolic mechanisms driving oxLDL-induced trained immunity in human primary monocytes and observed concomitant upregulation of glycolytic activity and oxygen consumption. In two separate cohorts of healthy volunteers, we assessed the impact of genetic variation in glycolytic genes on the training capacity of monocytes and found that variants mapped to glycolytic enzymes PFKFB3 and PFKP influenced trained immunity by oxLDL. Subsequent functional validation with inhibitors of glycolytic metabolism revealed dose-dependent inhibition of trained immunity in vitro. Furthermore, in vivo administration of the glucose metabolism modulator metformin abrogated the ability for human monocytes to mount a trained response to oxLDL. These findings underscore the importance of cellular metabolism for oxLDL-induced trained immunity and highlight potential immunomodulatory strategies for clinical management of atherosclerosis. Key messages Brief stimulation of monocytes to oxLDL induces a prolonged inflammatory phenotype. This is due to upregulation of glycolytic metabolism. Genetic variation in glycolytic genes modulates oxLDL-induced trained immunity. Pharmacological inhibition of glycolysis prevents trained immunity.

Removal of chromium from wastewater by swine hair residues applied as a putative biofilter - Orlando de Paris Júnior; Thamarys Scapini; Aline Frumi Camargo; Bruno Venturin; Caroline Dalastra; Simone Kubeneck; Fabiane Fernanda Czapela; Karina P. Preczeski; Fábio Spitza Stefanski; Eduardo Pavan Korf; Alexsandra Valério; Marco Di Luccio; et al. (Environmental Science and Pollution Research, 2019)

Two epizootic Perkinsus spp. events in commercial oyster farms at Santa Catarina, Brazil - Ana C. Luz Cunha; Vitor de A. Pontinha; Maria Alcina M. de Castro; Simone Sühnel; Sthefanie C. Medeiros; Ângela M. Moura da Luz; Ricardo Harakava; Leonardo Tachibana; Danielle F. Mello; Naissa M. Danielli; Alcir L. Dafre; Aimê R. M. Magalhães; et al. (Journal of Fish Diseases, 2019)
Perkinsus spp. have been detected in various bivalve species from north‐east Brazil. Santa Catarina is a South Brasil state with the highest national oyster production. Considering the pathogenicity of some Perkinsus spp., a study was carried out to survey perkinsosis in two oyster species cultured in this State, the mangrove oyster Crassostrea gasar and the Pacific oyster Crassostrea gigas . Sampling involved eight sites along the state coast, and oyster sampling was collected during the period between January 2013 and December 2014. For the detection of Perkinsus , Ray's fluid thioglycollate medium (RFTM) and histology were used, and for the identification of the species, PCR and DNA sequencing were used. Perkinsus spp. was found by RFTM in C. gigas and C. gasar from São Francisco do Sul. This pathology was also detected in C. gasar from Balneário Barra do Sul both, by RFTM and histology. Perkinsus marinus was identified in C. gigas and C. gasar from São Francisco do Sul and Perkinsus beihaiensis in C. gasar from Balneário Barra do Sul. This is the first report of P. marinus in C. gigas from South America. Results of this preliminary study suggest that both oyster species tolerate the species of Perkinsus identified, without suffering heavy lesions.

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Irreversible electroporation as treatment of locally advanced and as margin accentuation in borderline resectable pancreatic adenocarcinoma - P. Marsanic; A. Mellano; A. Sottile; M. De Simone (Medical & Biological Engineering & Computing, 2017)

Biological aspects of Bemisia tabaci biotype B and the chemical causes of resistance in soybean genotypes - Simone S. Vieira; André L. Lourenção; José P. da Graça; Tatiani Janegitz; Mariana C. Salvador; Maria Cristina N. de Oliveira; Clara Beatriz Hoffmann-Campo (Arthropod-Plant Interactions, 2016)

“Watching the Detectives” report of the general assembly of the EU project DETECTIVE Brussels, 24–25 November 2015 - Ruani N. Fernando; Umesh Chaudhari; Sylvia E. Escher; Jan G. Hengstler; Jürgen Hescheler; Paul Jennings; Hector C. Keun; Jos C. S. Kleinjans; Raivo Kolde; Laxmikanth Kollipara; Annette Kopp-Schneider; Alice Limonciel; et al. (Archives of Toxicology, 2016)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Recurrent Varicella following Steroids and Fingolimod in a Multiple Sclerosis Patient - D. Ferraro; S. De Biasi; F. Vitetta; A. M. Simone; L. Federzoni; V. Borghi; A. Cossarizza; P. F. Nichelli; P. Sola (Journal of Neuroimmune Pharmacology, 2013)

Patterns, processes and vulnerability of Southern Ocean benthos: a decadal leap in knowledge and understanding - Stefanie Kaiser; Simone N. Brandão; Saskia Brix; David K. A. Barnes; David A. Bowden; Jeroen Ingels; Florian Leese; Stefano Schiaparelli; Claudia P. Arango; Renuka Badhe; Narissa Bax; Magdalena Blazewicz-Paszkowycz; et al. (Marine Biology, 2013)

Value-based healthcare in Lynch syndrome - Simone D. Hennink; Nandy Hofland; Jessica P. Gopie; Corinne van der Kaa; Kimberley de Koning; Maartje Nielsen; Carli Tops; Hans Morreau; Wouter H. de Vos tot Nederveen Cappel; Alexandra M. J. Langers; James C. Hardwick; Katja N. Gaarenstroom; et al. (Familial Cancer, 2013)

Asbestos Risk: From Raw Material to Waste Management: The Italian Experience - F. Paglietti; S. Malinconico; V. Di Molfetta; S. Bellagamba; F. Damiani; F. Gennari; P. De Simone; F. Sallusti; M. Giangrasso (Critical Reviews in Environmental Science and Technology, 2012)

Endothelial colony-forming cells show a mature transcriptional response to shear stress - Anastasia D. Egorova; Marco C. DeRuiter; Hetty C. de Boer; Simone van de Pas; Adriana C. Gittenberger-de Groot; Anton J. van Zonneveld; Robert E. Poelmann; Beerend P. Hierck (In Vitro Cellular & Developmental Biology - Animal, 2012)

Pharmacokinetics and protein binding of cefazolin in morbidly obese patients - Simone van Kralingen; Margot Taks; Jeroen Diepstraten; Ewoudt M. van de Garde; Eric P. van Dongen; Marinus J. Wiezer; Bert van Ramshorst; Bart Vlaminckx; Vera H. Deneer; Catherijne A. Knibbe (European Journal of Clinical Pharmacology, 2011)

Unraveling new genes associated with seed development and metabolism in Bixa orellana L. by expressed sequence tag (EST) analysis - Virgínia L. F. Soares; Simone M. Rodrigues; Tahise M. de Oliveira; Talisson O. de Queiroz; Lívia S. Lima; Braz T. Hora-Júnior; Karina P. Gramacho; Fabienne Micheli; Júlio C. M. Cascardo; Wagner C. Otoni; Abelmon S. Gesteira; Marcio G. C. Costa (Molecular Biology Reports, 2011)

Detection of cross-infection associated to a Brazilian PCR-ribotype of Clostridium difficile in a university hospital in Rio de Janeiro, Brazil - Ilana T. Balassiano; Joaquim dos Santos-Filho; Juliana M. Vital-Brazil; Simone A. Nouér; Claudia R. C. Souza; Jon S. Brazier; Eliane de O. Ferreira; Regina M. C. P. Domingues (Antonie van Leeuwenhoek, 2011)

Erratum to: Involvement of sensory nerves and TRPV1 receptors in the rat airway inflammatory response to two environment pollutants: diesel exhaust particles (DEP) and 1,2-naphthoquinone (1,2-NQ) - Aila Mirtes Teles; Yoshito Kumagai; Susan D. Brain; Simone A. Teixeira; Ana A. Varriano; Maria Alice A. G. Barreto; Wothan Tavares de Lima; Edson Antunes; Marcelo N. Muscará; Soraia K. P. Costa (Archives of Toxicology, 2010)

Involvement of sensory nerves and TRPV1 receptors in the rat airway inflammatory response to two environment pollutants: diesel exhaust particles (DEP) and 1,2-naphthoquinone (1,2-NQ) - Aila Mirtes Teles; Yoshito Kumagai; Susan D. Brain; Simone A. Teixeira; Ana A. Varriano; Maria Alice A. G. Barreto; Wothan Tavares de Lima; Edson Antunes; Marcelo N. Muscará; Soraia K. P. Costa (Archives of Toxicology, 2010)

Identification and characterization of proteases from skin mucus of tambacu, a Neotropical hybrid fish - C. M. C. Salles; P. Gagliano; S. A. T. Leitão; J. B. Salles; H. L. M. Guedes; V. P. F. Cassano; S. Giovanni De-Simone (Fish Physiology and Biochemistry, 2007)

Localization of granulatimide alkaloids in the tissues of the ascidian Didemnum granulatum - Mirna H. R. Seleghim; Simone P. de Lira; Patrícia T. Campana; Roberto G. S. Berlinck; Marcio R. Custódio (Marine Biology, 2007)

Regulation of ventilation in the caiman (Caiman latirostris): effects of inspired CO2 on pulmonary and upper airway chemoreceptors - Glenn J. Tattersall; Denis V. de Andrade; Simone P. Brito; Augusto S. Abe; William K. Milsom (Journal of Comparative Physiology B, 2006)

Programmed cell death during the transition from multicellular structures to globular embryos in barley androgenesis - Simone de F. Maraschin; Gwénaël Gaussand; Amada Pulido; Adela Olmedilla; Gerda E. M. Lamers; Henrie Korthout; Herman P. Spaink; Mei Wang (Planta, 2005)

Time-lapse tracking of barley androgenesis reveals position-determined cell death within pro-embryos - Simone de F. Maraschin; Marco Vennik; Gerda E. M. Lamers; Herman P. Spaink; Mei Wang (Planta, 2005)